أثر الاختلافات الثقافية والاجتماعية على تغليف المنتج الدولي دراسة ميدانية على شركات تكرير وتعبئة الزيوت في الساحل السوري - قاسم سامر; وحود نور حسن (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف البحث إلى دراسة أثر الاختلافات الثقافية والاجتماعية والمتمثلة بـ (اللغة, علم الجمال, العادات والتقاليد, الأسرة, المرأة, التعليم, الجماعات المرجعية) على عملية تغليف المنتج الدولي. ولتحقيق أهداف البحث تمّ بناء استبانة وتوزيعها على العاملين في شركات تكرير وتعبئة الزيوت في الساحل السوري, وقد بلغ عدد الاستمارات الموزعة (122) استمارة, حيث أعيد منها (113) استمارة كاملة وصالحة للتحليل الإحصائي, وبنسبة إجابة بلغت (92.62%). وباستخدام الأساليب الإحصائية المناسبة كان من أهم النتائج: 1- تؤثر الاختلافات الثقافية والاجتماعية (الأسرة, المرأة, التعليم) على عملية تغليف المنتج الدولي, حيث تبين وجود علاقة ارتباط معنوية ومتينة جداً بين هذه العوامل وعملية تغليف المنتج الدولي. 2- تؤثر الاختلافات الثقافية والاجتماعية (اللغة, علم الجمال, العادات والتقاليد, الجماعات المرجعية) على عملية تغليف المنتج الدولي, حيث تبين وجود علاقة ارتباط معنوية ومتينة بين هذه العوامل وعملية تغليف المنتج الدولي. The research aims to study the impact of cultural and social differences, namely (language, aesthetics, customs and traditions, family, women, education, reference groups) on the process of international product packaging. To achieve the objectives of the research were built identify and Toseahaaly workers in companies food industry in the Syrian coast (refining and filling oils), The number of questionnaires distributed (122) form, where the re-ones (113) form a complete and valid for statistical analysis, and by answer was (92.62%) . And using appropriate statistical methods was one of the most important results: 1-affect cultural and social differences (family, women, education) on the process of international product packaging, where it was found a significant correlation and a very tough between these factors and the process of international product packaging. 2-affect social and cultural differences (language, aesthetics, customs and traditions, reference groups) on the process of international product packaging, where it was found a significant correlation strong between these factors and the process of international product packaging.